Pseudotumor Cerebri Complicating Measles - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A novel case of pseudotumor cerebri (PTC) that presented in an 8-year-old girl 3 weeks after measles is reported from Ondokuz Mayis University, Samsun, Turkey.